2020
DOI: 10.3390/w12010289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Stress on Fluorescence Parameters and Photosynthetic Characteristics of Drip Irrigation in Rice

Abstract: To study the effects of water stress on the fluorescence parameters and photosynthetic characteristics of rice under drip irrigation and mulching, so as to determine the response mechanisms to water stress during the tillering stage. A two-year trial was carried out at Shihezi University, China. Three water gradients were investigated. The results showed that the chlorophyll content (a + b), photosynthetic rate (Pn), and leaf area index (LAI) decreased with decreasing soil moisture content at the tillering sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 19 publications
4
39
0
1
Order By: Relevance
“…The results show a decrease in this fluorescence parameter due to the different concentration of APAP in the substrate. The above conclusions are consistent with [ 61 , 62 ]. Related issues are reported in [ 63 ], who studied the effect of heavy metals on the alga Halophila ovalis .…”
Section: Resultssupporting
confidence: 92%
“…The results show a decrease in this fluorescence parameter due to the different concentration of APAP in the substrate. The above conclusions are consistent with [ 61 , 62 ]. Related issues are reported in [ 63 ], who studied the effect of heavy metals on the alga Halophila ovalis .…”
Section: Resultssupporting
confidence: 92%
“…In accordance with our data, a previous study [ 26 ] also demonstrated that drought stress strongly suppressed the utilization of the excitation energy by photochemistry, causing an inhibition of the electron transport rate and Ф PSII , as well as reduction of the PSII acceptor side (q p ), connected with an increased thermal dissipated energy (i.e., higher non-photochemical quenching, NPQ values). More recent studies have also shown that drought stress had a significant negative effect on photosynthetic characteristics and chlorophyll content in rice plants [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the competition between these three processes, ChlF can be used to obtain photosynthesis information (Maxwell & Johnson, 2000;Murchie & Lawson, 2013). In recent years, researchers have used the changes of ChlF to explore photosynthetic apparatus under different environmental situations (Badr & Brueggemann, 2020;Hajihashemi et al, 2020;Iqbal et al, 2019;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%